2012
DOI: 10.1016/j.jacc.2012.08.878
|View full text |Cite
|
Sign up to set email alerts
|

TCT-832 Epidemiology of Severe Aortic Stenosis in the Elderly: A Systematic Review and Meta-Analysis of Published Prevalence Estimates

Abstract: Background:The prevalence of degenerative Aortic Stenosis (AS) is strongly linked to the phenomenon of population aging. While elderly patients form the majority of patients treated with AS, comorbidities place them at high for surgical aortic valve replacement (SAVR). With the new treatment option of transcatheter aortic valve implantation (TAVI), also patients formerly deemed inoperable can now be treated. Robust estimates in an elderly population remain unclear. The objective of this study is to perform a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…A systematic review by Strachan and colleagues [1] found that 4.3% of persons aged over 75 met the criterion of severe AS of having an aortic valve area (AVA) less than 1 cm. Surgical aortic valve replacement has been used for decades as the gold standard treatment for AS [2].…”
mentioning
confidence: 99%
“…A systematic review by Strachan and colleagues [1] found that 4.3% of persons aged over 75 met the criterion of severe AS of having an aortic valve area (AVA) less than 1 cm. Surgical aortic valve replacement has been used for decades as the gold standard treatment for AS [2].…”
mentioning
confidence: 99%